Economic Und Fiscal Effects of the FIFA World Cup in Germany - the Case of Munich - Alina Mihaela Popescu; Peter Friedrich; Gunther Wonnemann (European Regional Science Association (ERSA), 2006)
The authors determine the income effects, employment effects, production effects, migration effects as well as the budget effects and effects concerning social insurances. These effects concern the city of Munich, the hinterland, other municipalities, Bavaria, other states and the federation. The so-called "Taxonomic Localization Approach for Public Offices" is applied. The model for identifying the effects considers the characteristics of the games and of the Munich region. Direct effects are related to economic units directly involved in the World Cup™ games. Indirect effects concern the reaction of economic units which are not part of the project, e.g. hotels in Munich. A project includes the effects of the visitors and accompanying persons, of journalists, of a media centre, of FIFA-congresses and of special social events related to the games organized by the city of Munich. In addition, activities of fan-shops, restaurants, service and marketing companies, of the FIFA, the firm operating the stadium influence the size of the effects. The effects are estimated for the year 2006. In Munich, the effects on income, employment, and production turn out considerable high. The budget effects to the city of Munich are also positive. These are going to be positive for the hinterland and the social insurance, too. The size of the effects depend mainly on the visitors and journalists as well as on their expenses. Positive effects caused by the World Cup™ games in Munich compensate the losses of other regions. Moreover, the business and financial conditions of the stadium, the intergovernmental horizontal and vertical fiscal relations, the characteristics of the regional economy, number of visitors, etc. determine the effects. Public relation effects for Munich, social and political effects and promotion of sports occur, but are not considered here.
Keywords: 330